PROSEDUR PENGUJIAN SUBSTANTIF AKUN ASET TETAP PT RTZ OLEH KANTOR AKUNTAN PUBLIK JEPTHA, NASIB, DAN JUNIHOL - Rizky Ahmad Fauzan (2021)
Substantive Testing is an audit procedure that has been designed and made by the auditor to test and detect material misstatements that can affect the truth of the balances in the financial statements. Fixed assets are equipment used by the company in supporting its operations to generate revenue. The Substantive Testing of this fixed asset account was carried out by the Public Accounting Firm (KAP) of Jeptha, Nasib, and Junihol on PT. RTZ which is a company engaged in the service and maintenance of roads. This report aims to inform how the process of substantive testing procedures for fixed asset accounts is carried out. The implementation of this substantive test is carried out systematically starting from audit planning, testing the company's internal controls, and carrying out substantive tests in accordance with the existing audit program. In the audit program there are also several activities carried out, such as carrying out analytical procedures, performing physical checks on fixed assets, checking authorization for fixed assets, and calculating depreciation of fixed assets. From some of the activities above, it can be concluded that the fixed asset accounts of PT RTZ in 2020 have been presented fairly and no material misstatements were found.